PERKEMBANGAN MAKNA PEYORATIF PADA KATA BAHASA INGGRIS â€˜IDIOTâ€™: SEBUAH KAJIAN ETIMOLOGI - Ajurah, Nur (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2018)
This study argues that every word of any natural language is prone to meaning modification known as pejoration. Pejoration happens when a meaning of words becomes negative and it is different from its original meaning. In order to answer that phenomenon, this study entitled â€œPejorative Development of English Word â€˜Idiotâ€™: A Study of Etymologyâ€ issues that the English word â€˜idiotâ€™ may have experienced pejoration. It discusses the history of the word idiotâ€™ and its pejorative development. Liberman and Voylesâ€™s theories are used in this study. In the analysis, Libermanâ€™s theory is applied to explain the history of the word â€˜idiotâ€™ and also the development of its meaning, while Voylesâ€™s theory is adapted to see the semantic features of the word â€˜idiotâ€™ whether the meaning is specific or general. The descriptive qualitative method is used to explain the phenomena covered in pejorative datum. The datum was analyzed and described using applying grand and supporting theories mentioned earlier. The result shows that the word â€˜idiotâ€™ has experienced degradation of meaning where the word itself in its original meaning meant â€˜a private personâ€™, but over time it has acquired a negative connotation. The word is currently used in the sense of â€˜a stupid person or someone has done something stupidâ€™ or â€˜someone who is mentally ill or has a very low level of intelligenceâ€™.